1978
DOI: 10.2134/agronj1978.00021962007000010027x
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting in Cotton as Affected by Controlled Boll Set1

Abstract: Environmental stress and boll load have both been suggested as responsible for the fruiting cessation (cut out) that occurs in cotton (Gossypium hirsutum L.) in mid‐summer in the hot, desert southwestern USA. This study was conducted to examine the influence of boll load on the flowering hiatus. Two cultivars differing in growth habit were planted in the field on an Avondale clay loam soil, a member of the fine, loamy, mixed Hyperthermic Torrifluventic Haplustolls. ‘Deltapine Smooth Leaf’ (DpSL) has a more det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…A smaller plant fruit load corresponds to less internal competition for available resources and, hence, a greater flower setting (Patterson et al. ). Observations conducted for 7 years demonstrated a correlation between the minimum temperatures (NTs) and the number of bolls set on the plant (Fisher ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller plant fruit load corresponds to less internal competition for available resources and, hence, a greater flower setting (Patterson et al. ). Observations conducted for 7 years demonstrated a correlation between the minimum temperatures (NTs) and the number of bolls set on the plant (Fisher ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the percentage of plants with bolls was only 20 % for those plants that grew under HNTs in the floral bud stage against 54 % and 55 % for those subjected to stress in the flowering stage and the control treatment, respectively. A smaller plant fruit load corresponds to less internal competition for available resources and, hence, a greater flower setting (Patterson et al 1978). Observations conducted for 7 years demonstrated a correlation between the minimum temperatures (NTs) and the number of bolls set on the plant (Fisher 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Compensation for early fruit removal in cotton has been of great interest to both agronomists and entomologists, as it will not only help in establishing the recovery potential, but also provide a good experimental condition to study association between source and sink, as well as vegetative and reproductive growth (Dong et al 2008b;Zhang et al 2008). Numerous fruit removal studies have shown that reproductive sink removal enhances vegetative growth and development (Patterson et al 1978;Kennedy et al 1986;Ungar et al 1987;Jones et al 1996). Loss of early fruiting forms has also been shown to increase root growth (Sadras 1996;Dumka et al 2004), alter spatial yield distribution (Bednarz and Roberts 2001), and improve Cry1AC expression of transgenic Bacillus thuringiensis Berliner (Bt) cotton (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Guinn (1985) reported that flowers or bolls removal at first node has increased boll retention at second node. Patterson et al (1978) also, reported that at an early stage flowers removal has increased flowering and fruiting.…”
Section: Introductionmentioning
confidence: 88%